Optimization of surface quality in precision grinding using diamond wheels with variable grain composition - Kulina, Dmytro (National Technical University "Kharkiv Polytechnic Institute", 2025)
The paper presents a study on the influence of diamond grinding wheels with variable grain composition on surface quality during precision grinding of hard-to-machine materials. The research examines how combinations of fine and coarse abrasive grains within a single tool affect surface roughness, thermal load, and tool wear. Grinding tests were conducted under dry and semi-dry conditions using solid lubricating materials. The results show that wheels with mixed grain sizes offer a balance between high material removal rates and improved surface finish, with notable reductions in cutting force and post-contact temperature compared to wheels with uniform grain size. The findings can guide the development of advanced grinding technologies for components made of titanium alloys and heat-resistant steels.
Keywords: diamond grinding wheels; variable grain composition; precision grinding; hard-to-machine materials; titanium alloy; surface roughness; thermal effects